2012
DOI: 10.2174/092986712802430090
|View full text |Cite
|
Sign up to set email alerts
|

Pyrazine Functionalized Ag(I) and Au(I)-NHC Complexes are Potential Antibacterial Agents

Abstract: Antimicrobial resistance is an ever-increasing problem throughout the world and has already reached severe proportions. Bacteria can develop ways to render traditional antibiotics ineffective, raising a crucial need to find new antimicrobials with novel mode of action. We demonstrate here a novel class of pyrazine functionalized Ag(I) and Au(I)-NHC complexes as antibacterial agents against human pathogens that are resistant to several antibiotics. Complete synthetic and structural studies of Au(I) and Ag(I) co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(46 citation statements)
references
References 52 publications
1
45
0
Order By: Relevance
“…Over the past couple of decades, a broad range of silver(I) complexes supported by NHCs has been synthesized [25] and applied for biological screening [26]. More recently, Ag(I)eNHC complexes were found to be potent agents against drug-resistant pathogens [27,28] and recent studies by Youngs and others have shown that AgeNHCs are useful in antibacterial and anticancer applications [28].…”
Section: Com-plex Experimental Theoreticalmentioning
confidence: 99%
“…Over the past couple of decades, a broad range of silver(I) complexes supported by NHCs has been synthesized [25] and applied for biological screening [26]. More recently, Ag(I)eNHC complexes were found to be potent agents against drug-resistant pathogens [27,28] and recent studies by Youngs and others have shown that AgeNHCs are useful in antibacterial and anticancer applications [28].…”
Section: Com-plex Experimental Theoreticalmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11][12] Beyond catalysis, M-NHCs recently contributed interesting results as promising antimicrobial and anticancer drugs. [10][11][12][13][14][15] Though initially the imidazoline NHC ligands comprised N-alkylated derivatives, the file is enriched with N-functionalized NHC by pyridine, pyrimidine, pyrazole, oxazole, thiazole, carbazole, etc. [2][3][4][5][6][7][8][9]14,15] Most of N-alkylated NHCs acts as mono dentate ligands, whereas incorporation of wingtip such as pyridine/pyrimidine/oxazole/thiazole in the backbone offers either mono-, bi-, or tridentate NHC depending upon the designing of the ligand and choice of metal.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14][15] Though initially the imidazoline NHC ligands comprised N-alkylated derivatives, the file is enriched with N-functionalized NHC by pyridine, pyrimidine, pyrazole, oxazole, thiazole, carbazole, etc. [2][3][4][5][6][7][8][9]14,15] Most of N-alkylated NHCs acts as mono dentate ligands, whereas incorporation of wingtip such as pyridine/pyrimidine/oxazole/thiazole in the backbone offers either mono-, bi-, or tridentate NHC depending upon the designing of the ligand and choice of metal. As NHC ligand is a strong σ-donor and weak π-acceptor than phosphine, it is used as an alternative of phosphine in catalysis.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations